Integrating e-portfolios into L2 classrooms : education for future - Lam, Ricky (Multilingual Matters, 2024)
"This book explains both the theory and practice of e-Portfolio pedagogy and assessment in second and foreign language classroom contexts. In addition to providing new insights for scholars of language pedagogy, the book equips language teachers with the practical knowledge and skills they need to use the e-Portfolio approach in their classrooms"-- Provided by publisher.
Keywords: Language and languages -- Computer-assisted instruction.; Electronic portfolios in education.; Langage et langues -- Enseignement assisté par ordinateur.; Portfolios électroniques en éducation.; LANGUAGE ARTS & DISCIPLINES / Study & Teaching